THE EFFECTS OF CIRC TECHNIQUE ON STUDENT PARTICIPATION IN TEACHING READING COMPREHENSION OF NARRATIVE TEXT :A Quasi Experimental Study of the First Grade Students at one Private Senior High School in Bandung - Agnia Nur Afifah, - (2011)
Reading, as student input to learn new vocabulary and information, is important to be mastered. Teacher arrangement of class activities should encourage student to improve the reading comprehension. This classroom activity is expected to facilitate students to participate in classroom discussion. This paper reports the effects of CIRC technique on student reading comprehension of narrative text and the student classroom participation using the technique. This quasi experimental study is conducted at first grader at one private senior high school in Bandung. Two groups are compared in order to see the effects of CIRC. The instruments used to answer the research questions are reading comprehension test and observation sheet. To investigate student reading comprehension, posttest is analyzed by using independent t-test to identify whether there is a difference in students' reading comprehension of narrative text between control and experimental group. Observation sheet is analyzed as student classroom participation of spontaneous interaction to find out the effect of CIRC on student participation. The result shows that: 1) CIRC can facilitate students to improve their reading comprehension of narrative text established by statistic computation (tobt > tcrit or 3.073 > 2.000). 2) Student classroom participation in experimental class that uses CIRC is higher than in control class that implements lecturing technique. Students participation improvement is in the category of answering questions, talking about the topic, giving opinions, participating in discussion, making comments and asking questions. Based on the findings, it is recommended to use CIRC technique in teaching reading comprehension of narrative text. Moreover, further research is suggested to carry out qualitative study on student participation in using CIRC technique.